Attachment Security Priming Delayed Negative Information-Related Attentional Disengagement Among Anxiously Attached Individuals: Evidence From Behavioral and Functional MRI Experiments - Wang, Beiyi; Peng, Xinyuan; Gao, Fei; Zhang, Kaihua; Zhang, Jianxin; Wu, Lili (Frontiers in Psychology, 2022)
Although attachment security has been found to attenuate people’s experience of unpleasant information, how it modulates the attentional process toward such information remains unknown. The present study examined this issue by employing the dot-probe task in functional MRI. After completing the Experiences in Close Relationships-Revised questionnaire (ECR-R), 39 participants were asked to complete the dot-probe task in two conditions: the attachment security priming condition and neutral priming condition. The behavioral results revealed that individuals with high level of attachment anxiety exhibited larger attention disengagement from negative traits in the security priming condition than in the control condition. Correspondingly, the brain regions involved in attention regulation and shifting, such as the posterior cingulate and bilateral parietal area, were less activated among high anxiously attached individuals in the security priming condition. These results suggest a role of attachment security priming in regulating the emotional response in anxiously attached individuals during the attentional stage.